Multidimensional insights of electrochemical and quantum investigations of morpholinium cationic surfactants as corrosion inhibitors for carbon steel in acidic solution - A. Elaraby; Doaa F. Seyam; Sherine A. Abdelkader (Scientific Reports)
Abstract Three novel morpholinium-cationic surfactants (coded: DCSM-8, DCSM-10, and DCSM-12) with chemical structure confirmed via FT-IR, HNMR, and mass analysis were applied for carbon steel (CS) corrosion control in acidic 4 M HCl solution. The investigated compounds decreased water surface tension (72 mN.m-1) to 19.85 mN.m-1 after the addition of DCSM-12. The surfactants mitigation performance was assessed via weight loss (W L ), potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS). The synthesized surfactants protected CS efficiently with higher inhibition efficiencies up to 97.029% at 1 × 10–3 M for DCSM-12 using PDP which also indicated that, the prepared surfactants inhibited both CS anodic and cathodic sites with cathodic dominant. EIS data showed higher CS resistance from 35.24 Ω.cm2 to 1245.54 Ω.cm2 after addition of 1 × 10–3 M for DCSM-12 with mitigation potency 97.17% which can be attributed to their adsorption process over CS surface forming a protective film layer that followed Langmuir adsorption isotherm reflecting the chemical adsorption affinity of the prepared mitigators with higher adsorption energy (ΔG*ads) values (> -40 kJ.mol-1). Also, the protection effect of the prepared inhibitor (DCSM-12) was confirmed using SEM (scanning electron microscopy) and EDX (energy-dispersive X-ray) showing improvement in CS surface morphology. The reactivity of the prepared surfactants and their mitigation role in CS deterioration were confirmed theoretically using DFT (density functional theory) and MCs (Monte Carlo simulations).